Effect of cinnamon essential oil and grape seed extract as functional‐natural additives in the production of cooked sausage‐impact on microbiological, physicochemical, lipid oxidation and sensory aspects, and fate of inoculated Clostridium perfringens. Issue 4 (28th February 2018) - Aminzare, Majid; Tajik, Hossein; Aliakbarlu, Javad; Hashemi, Mohammad; Raeisi, Mojtaba
Abstract: The present study was conducted to extend the shelf life of Lyoner‐type sausages during 40 days of storage at 4 °C with individual and combinational use of natural preservatives including cinnamon essential oil (CEO) and grape seed extract (GSE). The samples were analyzed for physicochemical properties (pH, aw, and color changes), lipid oxidation (thiobarbituric acid reactive substances [TBARS]), microbial quality (Lactic acid bacteria count, total viable count, psychrotrophic count, mold and yeast count, and fate of inoculated Clostridium perfringens ), and sensorial characteristics (taste, odor, color, texture, and overall acceptability) at 10‐day intervals. Results indicated that using GSE and CEO had higher Δ E (.55–1.56), a * (13.03–13.91), and lower L * (65.10–66.82), b * (15.40–16.65), whiteness index (59.45–60.60), TBARS values (2.91–3.28), and microbial counts than control at the end of storage time. Samples containing CEO .04%+ GSE .16% showed the best antimicrobial activity against C. perfringens (reduction of 1.72 log10 CFU/g at the end of storage time). Results also indicated that CEO addition and GSE addition improved odor and color scores of the samples, respectively. Therefore, use of CEO and GSE, especially in combination, is recommended to be applied in meat products. Practical applications: Nowadays, because of the adverse effects of chemical preservatives, application of multipurpose natural preservatives in small quantities is a more preferred approach. Therefore, to increase the shelf‐life and quality characteristics of meat products, new ingredient systems that are associated with natural and organic foods, are applied. The results of the present study showed the synergistic effects of combined use of CEO and GSE in maintaining the quality of fresh meat products as well as preventing their undesirable impacts on sensory attributes and physicochemical properties. Thus, combinational use of CEO and GSE due to extending the shelf life and safety of meat products can practically profit both producers and consumers.